Valmiki's Ramayana - Vālmīki; Pai, Anat
Amar Chitra Katha brings you Valmiki's Ramayana book- the Box Set, containing 960 pages (6 volumes) of colour and visual action in the graphic format. The story of Rama's childhood, his exile, Sita's abduction, Hanuman's devotion, and Ravana's death, form a heroic tale, which teaches numerous values. Valmikis Ramayana book illustrative and easy-to-read comic book set helps children not only learn about duty and honour, good and evil, love and loss, jealousy and destructive ambitions, it also helps develop their imagination and vocabulary